2006
DOI: 10.1051/0004-6361:20064879
|View full text |Cite
|
Sign up to set email alerts
|

The blue stragglers formed via mass transfer in old open clusters

Abstract: Aims. In this paper, we present the simulations for the primordial blue stragglers in the old open cluster M 67 based on detailed modelling of the evolutionary processes. The principal aim is to discuss the contribution of mass transfer between the components of close binaries to the blue straggler population in M 67. Methods. First, we followed the evolution of a binary of 1.4 M +0.9 M . The synthetic evolutionary track of the binary system revealed that a primordial blue straggler had a long lifetime in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 45 publications
5
89
0
1
Order By: Relevance
“…WOCS 4348, 4540 and 5379 in NGC 188, Gosnell et al 2014). The blue-straggler binaries during the mass-transfer phase have a "low-luminosity boundary" (about 0.75 mag brighter than the ZAMS) given by Tian et al (2006), and can match the observed red-sequence blue stragglers in globular cluster M30 (Ferraro et al 2009;Xin et al 2015). However, for the blue-straggler binaries that have finished mass transfer, including a blue straggler and a white dwarf (the BS-WD binaries), their locations in the color-magnitude diagram of M30 depend on the contribution of white dwarfs to the combined magnitudes of these binaries.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…WOCS 4348, 4540 and 5379 in NGC 188, Gosnell et al 2014). The blue-straggler binaries during the mass-transfer phase have a "low-luminosity boundary" (about 0.75 mag brighter than the ZAMS) given by Tian et al (2006), and can match the observed red-sequence blue stragglers in globular cluster M30 (Ferraro et al 2009;Xin et al 2015). However, for the blue-straggler binaries that have finished mass transfer, including a blue straggler and a white dwarf (the BS-WD binaries), their locations in the color-magnitude diagram of M30 depend on the contribution of white dwarfs to the combined magnitudes of these binaries.…”
Section: Introductionmentioning
confidence: 79%
“…Hence, the formation of both sequences may be related to the binary evolution. Meanwhile, Lu et al (2010) found that some blue stragglers produced by Case B binary evolution are below the low-luminosity boundary given by Tian et al (2006). Chen & Han (2008a) show that binary merger can produce single blue stragglers very close to or even below the zero-age main sequence (ZAMS), i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, models of MS+WD blue straggler systems were constructed by Tian et al (2006) but they cannot take their calculations through the final common envelope phase. Regarding the MS+WD phase, however, they find quite similar results to ours despite their use of a full stellar evolution rather than synthetic code.…”
Section: Progenitors Observedmentioning
confidence: 99%
“…Blue stragglers formed via mass transfer in old open clusters M67 has been studied (Tian et al 2006). So we focus on case A binaries in young clusters.…”
Section: P Lu and L Dengmentioning
confidence: 99%